2017
DOI: 10.3390/ijms18030615
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Midpalatal Suture Changes after Rapid Maxillary Expansion in Growing Subjects: A Case Report

Abstract: The present case report aimed to investigate immediate histologic changes in midpalatal suture in humans following rapid maxillary expansion compared to control. Three patients (mean age 8.3 ± 0.9 years) were enrolled in the case report and underwent midpalatal suture biopsy. Two patients underwent treatment before biopsy. The third patient did not show transversal maxillary deficiency and was enrolled as a control. Biopsy samples of midpalatal suture at 7 (subject 1) and 30 days (subject 2) after maxillary ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
3
21
0
Order By: Relevance
“…Rapid maxillary expansion (RME) treatment is the treatment most commonly used by clinicians [9], though slow maxillary expansion (SME) is being employed more often [10]. The effects of palatal expansion are mainly skeletal and related to the upper arch transverse dimensions, however dental and respiratory function changes are often present [11][12][13][14][15][16][17]. According to a recent systematic review and meta-analysis, the current evidence on the dental and skeletal effects was reported to be of a higher level for RME than SME, but the two expansion protocols seemed to have no significant differences in dentoalveolar transversal effects [17].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid maxillary expansion (RME) treatment is the treatment most commonly used by clinicians [9], though slow maxillary expansion (SME) is being employed more often [10]. The effects of palatal expansion are mainly skeletal and related to the upper arch transverse dimensions, however dental and respiratory function changes are often present [11][12][13][14][15][16][17]. According to a recent systematic review and meta-analysis, the current evidence on the dental and skeletal effects was reported to be of a higher level for RME than SME, but the two expansion protocols seemed to have no significant differences in dentoalveolar transversal effects [17].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid maxillary expansion (RME) is a common orthodontic treatment procedure for correcting transverse maxillary deficiency. The original indication for RME was to increase the transverse width of a narrow maxilla, but it is clinically proven that the effects of the expansion are more over the whole nasomaxillary complex …”
Section: Introductionmentioning
confidence: 99%
“…Further investigations are necessary to identify new stable points (outside dental arch) to perform this important step. Probably in the future, considering how digital technology is evolving fast in all the fields of dentistry [ 46 - 48 ], this entire process would be automatic, which could then make this methodology clinically useful in treatment planning and monitoring not only for fixed orthodontics but also for interceptive treatment [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%